الدولة المثالية في المجتمع الإسلامي: مناقشات وردود - Muslihun Muslihun (Universitas Yudharta Pasuruan, 2019)
This article aims to explain about ideality state in Islamic discourse on the history muslim society. Drawing on empirical cases from Arabic kingdom and a comparative literature of medina constitution, this article reveals a dilemma within our life in nation-state system,and the other hand, Islamic state arising, appearing and developing with a revitalization doctrine back to al-Quran and Sunnah nabawiah. Firstly, Islam is a religion not determine of Islamic state during of Muhammad PBUH. life. Secondly, the concept of Islam for civil society is justice, humanity, and liberty. So, if not contradictory with this three spirit then the government or nation called by muslim society.